Oranges - (:unkn) unknown (The Bonanza. Smith Bros. and Co., Trinidad, 2009)
A picture of a bunch of oranges on a branch.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fruit--Trinidad and Tobago; Tropical fruit--Trinidad and Tobago; [1920]